Et in Arcadia Ego - Basson, Steve (The Society of Architectural Historians, Australia and New Zealand, 1999)
Through our traditional and contemporary readings of history, the architectural subject has generally been cast into the role of cultural object, whose purposes, organization and modes of representation are directed, as aterna veritas, towards outcomes born of purely architectural and artistic forces. This carries with it an interpretative focus that conceives the past as a realm invested with the same culturally authoritative reasons and needs for building as our own and as such, overlays the organizational and perceptual conditions that empowered, for each differing age, their own motives and necessities for building. The question raised here is that the past is ever an invention of the present and that, conventionally, the historicized architectural object denotes a constructed subject manufactured out of our own conditions and surfaces of possibility. The following paper seeks to explore this question of historical focus and analysis through an outline series of readings that emerge out the medieval church form which draw upon the order of spatial imperatives, significations, meanings and rituals that underscored its own possibilities of production and reasons for being. Beginning from an allegorical rendering and positioning of these other possibilities, this paper will specifically move on to address the underlying conditions of church organization and production particular to the perceptual and discursive relations of the medieval era. These unfold around themes that concern resemblance, ideology, regulation and death. It is in these terms that this paper is aimed at reappraising our normalized view of the historicized architectural subject and at offering further avenues of analysis and interpretation of the Gothic church form.